The effect of practicum learning based audiovisual on students’ learning outcomes in Indonesian vocational secondary school - Cicilia Dyah Sulistyaningrum Indrawati; Patni Ninghardjanti; Chairul Huda Atma Dirgatama; Arif Wahyu Wirawan (Institute of Advanced Engineering and Science, 2022)
This research aimed to examine the effectiveness of practicum learning based audiovisual in improving students’ learning outcomes in vocational secondary schools. At the practical level, teachers play an important role in facilitating students by designing an appropriate method, media, and material of learning which represent the actual condition of workplaces. Thus, students can gain their learning skills and experiences. Quasi-experimental research was conducted in vocational secondary schools in Surakarta city, Indonesia. The research participants were 230 students categorized into the control group and the experimental group. The results showed the effectiveness of practicum learning based audiovisual in improving students’ learning outcomes effectively. The effectiveness can be proved by the average pretest score and post-test score between the control group and the experimental group. Considering its effectiveness, practicum learning based audiovisual can be used as an advanced model of learning in vocational secondary school especially in preparing students before joining the industrial circle. This research has shown the effectiveness of practicum learning based audiovisual in improving students’ learning outcomes in vocational secondary schools. It can be proved by the result of an independent t-test that shows significant differences in students’ learning outcomes in the control group and experimental group. Based on the results of research, the model of practicum based audiovisual learning can become an advanced model of practicum learning in vocational secondary schools, especially in non-engineering and technic majors.